2024
DOI: 10.3390/gels10040216
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hybrid Hydrogels: Next-Generation Biomaterials for Drug Delivery and Tissue Engineering

Md Mohosin Rana,
Hector De la Hoz Siegler

Abstract: Hydrogels, being hydrophilic polymer networks capable of absorbing and retaining aqueous fluids, hold significant promise in biomedical applications owing to their high water content, permeability, and structural similarity to the extracellular matrix. Recent chemical advancements have bolstered their versatility, facilitating the integration of the molecules guiding cellular activities and enabling their controlled activation under time constraints. However, conventional synthetic hydrogels suffer from inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 346 publications
0
3
0
Order By: Relevance
“…These networks, capable of absorbing and retaining substantial volumes of water, are distinguished by their remarkable ability to swell without dissolution, maintaining structural integrity through chemical or physical cross-linking mechanisms [9,10]. This intrinsic property allows hydrogels to mimic the physicochemical aspects of the natural extracellular matrix, making them particularly suited for applications in drug delivery systems [7,9,[11][12][13][14][15][16][17][18][19], tissue engineering [20][21][22][23][24], wound healing [25][26][27][28], and beyond, as illustrated in Figure 1. The initiation of hydrogel research and its expansion into biomedical sciences exemplify a trajectory of innovation, highlighting the versatility of these materials in solving complex biological challenges and their role in advancing biomedical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These networks, capable of absorbing and retaining substantial volumes of water, are distinguished by their remarkable ability to swell without dissolution, maintaining structural integrity through chemical or physical cross-linking mechanisms [9,10]. This intrinsic property allows hydrogels to mimic the physicochemical aspects of the natural extracellular matrix, making them particularly suited for applications in drug delivery systems [7,9,[11][12][13][14][15][16][17][18][19], tissue engineering [20][21][22][23][24], wound healing [25][26][27][28], and beyond, as illustrated in Figure 1. The initiation of hydrogel research and its expansion into biomedical sciences exemplify a trajectory of innovation, highlighting the versatility of these materials in solving complex biological challenges and their role in advancing biomedical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…PNIPAM is an acrylamide synthetic polymer for grafting of Chit backbones [20,23,34,35,37]. Chit-g-PNIPAM copolymers have been identified as potentially thermoresponsive and pHresponsive materials for drug delivery [38][39][40] and tissue engineering [41,42]. Additionally, it has been shown that they improve the oral delivery of hydrophobic medications, such as naproxen, caffeine, and paclitaxel, and favors the mucosal delivery of hydrophobic pharmaceuticals [40].…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials, hybrid systems combining synthetic polymers with natural biomolecules have emerged as promising candidates in the biomedical field, offering tailored properties and enhanced functionalities [5][6][7][8][9][10]. One of the most relevant examples is the combination of proteins with synthetic polymers [11,12], which has been demonstrated to affect cell adhesion, differentiation and proliferation and is thus appealing for applications such as drug delivery, tissue engineering and wound healing [5,[13][14][15][16]. In this context, the integration of poly(N-isopropylacrylamide) (PNIPAM) microgels with keratin, a fibrous protein, offers a promising approach for the development of novel biomaterials with a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%